GSH-sensitive polymeric prodrug: Synthesis and loading with photosensitizers as nanoscale chemo-photodynamic anti-cancer nanomedicine - Lei Luo; Yiming Qi; Hong Zhong; Shinan Jiang; Hu Zhang; Hao Cai; Yahui Wu; Zhongwei Gu; Qiyong Gong; Kui Luo (Elsevier, 2022)
Precisely delivering combinational therapeutic agents has become a crucial challenge for anti-tumor treatment. In this study, a novel redox-responsive polymeric prodrug (molecular weight, MW: 93.5 kDa) was produced by reversible addition-fragmentation chain transfer (RAFT) polymerization. The amphiphilic block polymer-doxorubicin (DOX) prodrug was employed to deliver a hydrophobic photosensitizer (PS), chlorin e6 (Ce6), and the as-prepared nanoscale system [NPs(Ce6)] was investigated as a chemo-photodynamic anti-cancer agent. The glutathione (GSH)-cleavable disulfide bond was inserted into the backbone of the polymer for biodegradation inside tumor cells, and DOX conjugated onto the polymer with a disulfide bond was successfully released intracellularly. NPs(Ce6) released DOX and Ce6 with their original molecular structures and degraded into segments with low MWs of 41.2 kDa in the presence of GSH. NPs(Ce6) showed a chemo-photodynamic therapeutic effect to kill 4T1 murine breast cancer cells, which was confirmed from a collapsed cell morphology, a lifted level in the intracellular reactive oxygen species, a reduced viability and induced apoptosis. Moreover, ex vivo fluorescence images indicated that NPs(Ce6) retained in the tumor, and exhibited a remarkable in vivo anticancer efficacy. The combinational therapy showed a significantly increased tumor growth inhibition (TGI, 58.53%). Therefore, the redox-responsive, amphiphilic block polymeric prodrug could have a great potential as a chemo-photodynamic anti-cancer agent.